2022
DOI: 10.3390/d14070572
|View full text |Cite
|
Sign up to set email alerts
|

Research Advances in Toona sinensis, a Traditional Chinese Medicinal Plant and Popular Vegetable in China

Abstract: Toona sinensis, a perennial and deciduous tree belonging to the Meliaceae family, has been cultivated for more than 2000 years in China. Storing the buds of T. sinensis is difficult, as it is easy for them to rot during storage, which seriously affects their edible and commodity value. Young leaves and buds of T. sinensis plants are excellent source of flavonoids, terpenoids, phenylpropanoids, and more. In addition, the bioactive components of T. sinensis possess numerous health benefits, such as antiviral, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Since the first WRKY proteins were identified, WRKY TFs have been well recognized in plants for their regulating functions in defense against abiotic and biotic stresses, growth and development, and secondary metabolism (Schluttenhofer and Yuan, 2015;Jiang et al, 2017;Abeysinghe et al, 2019). Terpenes are the signature volatile components of T. sinensis, and WRKYs are significantly involved in regulating the terpene pathway (Yang et al, 2012;Zhao et al, 2022). Neither the identification of the WRKY gene nor the regulation of terpenoids, the most iconic volatile substances in T. sinensis, has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first WRKY proteins were identified, WRKY TFs have been well recognized in plants for their regulating functions in defense against abiotic and biotic stresses, growth and development, and secondary metabolism (Schluttenhofer and Yuan, 2015;Jiang et al, 2017;Abeysinghe et al, 2019). Terpenes are the signature volatile components of T. sinensis, and WRKYs are significantly involved in regulating the terpene pathway (Yang et al, 2012;Zhao et al, 2022). Neither the identification of the WRKY gene nor the regulation of terpenoids, the most iconic volatile substances in T. sinensis, has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that the identified volatile components accounted for 92.58% of the total volatile oil. Among these components, caryophyllene has the highest content, reaching 19.51% (Zhao et al, 2022). Wang et al utilised GC-MS and relative odour activity values (ROAV) to examine the volatile components of T. sinensis sourced from the provinces of Guizhou, Yunnan, Sichuan and Shandong.…”
Section: Introductionmentioning
confidence: 99%
“…With its long-standing cultivation tradition, Toona sinensis is extensively grown as a woody vegetable in the northern and southern regions of China ( Peng et al., 2019 ). Due to the abundance of beneficial secondary metabolites found throughout the plant, it is extensively used in medicine, food production, and the chemical industry ( Cao et al., 2019 ; Zhao et al., 2022 ). The tender leaves of T. sinensis are particularly known for their unique aroma, which contributes to their widespread appreciation.…”
Section: Introductionmentioning
confidence: 99%
“…are sold at local markets in Korea ( Table 1 ). The extracts and compounds obtained from traditional GLVs (1–18) have been shown to possess antioxidant [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], anticancer [ 18 , 23 , 24 , 25 , 26 ], antiinflammation [ 20 , 25 , 27 , 28 ], anti-melanogenic [ 29 , 30 ], anti-fatigue [ 31 ], anti-obesity [ 32 , 33 ], antidiabetic [ 34 ], and immunostimulatory [ 35 ] activities. GLVs have abundant phytopigments.…”
Section: Introductionmentioning
confidence: 99%